Spatial issues in Arctic marine resource governance workshop summary and comment. (August 2015) - Kaiser, Brooks A.; Bakanev, Sergey; Bertelsen, Rasmus Gjedsø; Carson, Marcus; Eide, Arne; Fernandez, Linda; Halpin, Patrick; Izmalkov, Sergei; Kyhn, Line A.; Österblom, Henrik; Punt, Maarten; Ravn-Jonsen, Lars; et al.
Abstract: The rapidly changing Arctic marine ecosystems face new challenges and opportunities that are increasing and shifting governance needs in the region. A group of economists, ecologists, biologists, political scientists and resource managers met in Stockholm, SE, Sept 4–6, 2014 to discuss the governance of Arctic marine resources in a spatial context. We report on the findings here.